Rewiew: Paul McCartney grinds pepper in The Lives of John Lennon by Albert Goldman: behind the scenes with the Sgt. Pepper’s Lonely Hearts Club Band (Per Musi, 2022)
Review of the Paul grinds pepper chapter from the book The Lives of John Lennon (1988) by Albert Goldman, which brings relevant, little known and controversial data about the backstage of the LP album Sgt. Pepper's Lonely Hearts Club Band, released by the Beatles in 1967 and the compact disc with the tracks Penny Lane and Strawberry Fields forever, also released in 1967. It also brings the historical context that preceded the most radical aesthetic change in the Beatles' career, especially the recordings of the albums Rubber Soul (1965) and Revolver (1966).